Implementation of QR Code on E-Certificate for Events at Maranatha Christian University - Suteja, Bernard Renaldy; Imbar, Radiant; Johan, Meliana (SENATIK STT Adisutjipto, 2019)
Every participation in the activity is always proven by the presence of a certificate. Issuance of certificates requires fees for paper, printing and distribution. The emergence of the era of paper less should be able to transform the presence of the certificate. Paper less is stopped by the presence of digital documents that can be accessed independently (portable), easily and across platforms. Portable Document Format or abbreviated as PDF one of the popular documents that can be distributed via the internet. So that PDF can be used as a document base to realize e-Certificate. However, it is necessary to develop a good application to facilitate the presence of the e-Certificate, and present solutions related to the authenticity of the certificates produced.